Challenges in Acquisition of New Courses in Education, Bachelor of Technology in SD VS Traditional CSE Program: A Case Study of M.M. Deemed to Be University - Sharma, Arvind K; Sethi, Gunjan; Radley, Martin (International Journal of Computer Sciences and Engineering, 2019)
With rapid advancement in Technology and its demand in industry rapidly forcing Universities to take help of course content writers or open education resources to make changes in the existing curriculum, that must fulfill requirements of industries which they’re looking from fresh graduates. Even though development of new courses or enhancing the quality of existing courses by adding topics of more demanded technologies is a time consuming job yet as a result these time variant practices makes candidates job ready. In reality there are huge innovations in our lives based on engineering technology, but university curriculum not keeping pace. In this particular research article thorough study about bachelor level Software Development program discussed and suitable comparison with respect to existing program provided.